Unstable Atrial Fibrillation RVR and DNR: A Challenging Ethical Dilemma - Jeremiah J. Essig (Annals of Internal Medicine: Clinical Cases)
An 82-year-old man with history of dementia and atrial fibrillation (AF) was admitted for sepsis and subsequently developed AF with rapid ventricular response (RVR). Given a recent do not resuscitate (DNR) order, there was disagreement among providers regarding the use of direct current cardioversion (DCCV). This patient case reveals the ethical challenges faced by providers when patients with a DNR order develop unstable AF with RVR and discusses an ethical framework for decision-making regarding DCCV in patients with a DNR order. This case also promotes changes to clinical practice, such as discussing DCCV when discussing code status and replacing DNR with “no cardiopulmonary resuscitation.”